The centre cannot hold: Patterns of polarization in Nigeria - Fabio Clementi; Andrew L. Dabalen; Vasco Molini; Francesco Schettino (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
Our hypothesis is that Nigeria is going through a process of economic polarization. An analysis of this type is new for Nigeria; the limited availability of comparable data has hindered an investigation that requires data series not too close in time. The present paper tries to overcome this limitation by making use of recently developed survey-to-survey imputation techniques. To explore polarization, our study uses instead the relative distribution methodology. Findings confirm the sharp increase of polarization. Compared to 2003 consumption distribution is more concentrated in upper and lower defiles, while the middle defiles are progressively emptying out.
Keywords: C14; D30; D63; 330; Nigeria; consumption expenditure; inequality; polarization; relative distribution